Single and solid solutions metal carboxyphosphonates as precursors for phosphorous-containing electrocatalysts - López Vergara, Adrián; El-Refaei, S.M.; Russo, Patricia A.; Vilchez, A; Losilla, Enrique R.; Porras-Vázquez, José Manuel; Olivera-Pastor, Pascual; Pinna, N; Cabeza-Díaz, Aurelio (My University, 2019)
Co1-xFex-HPAA metal phosphonates were prepared and pyrolyzed under N2 and H2/Ar flows. The result-ing powders were structural and electrochemically characterised by XRD and CV, respectively. The ob-tained materials possess different structures depending on the temperature and pyrolysis atmosphere. Samples pyrolized in N2 at 1000 ºC are monophasic diphosphates, while phosphides form in H2/Ar at 850 ºC. Cyclic voltammetry studies indicate that the Co0.5Fe0.5HPAA sample, pyrolized in H2/Ar, exhibits the best behaviour, but further studies are needed to fully understand the role of graphene oxide and pyrazine.
Keywords: Química inorgánica; Elelctrocatalysis; Water splitting; Metal phosphonates; Metal phosphides